Probiotics for the treatment of upper and lower respiratory-tract infections in children: systematic review based on randomized clinical trials - Georgia Véras de Araujo; Mário Henriques de Oliveira Junior; Décio Medeiros Peixoto; Emanuel Sávio Cavalcanti Sarinho (Jornal de Pediatria, 2015)
ABSTRACT OBJECTIVES: Evaluate the effect of probiotics on the symptoms, duration of disease, and the occurrence of new episodes of upper and lower respiratory infections in healthy children. SOURCES: In order to identify eligible randomized controlled trials, two reviewers accessed four electronic databases [MEDLINE/PubMed, Scopus (Elsevier), Web of Science, and Cochrane (Cochrane VHL)], as well as ClinicalTrials.gov until January 2015. Descriptors were determined by using the Medical Subject Headings tool, following the same search protocol. SUMMARY OF THE FINDINGS: Studies showed to be heterogeneous regarding strains of probiotics, the mode of administration, the time of use, and outcomes. The present review identified 11 peer-reviewed, randomized clinical trials, which analyzed a total of 2417 children up to 10 incomplete years of age. In the analysis of the studies, reduction in new episodes of disease was a favorable outcome for the use of probiotics in the treatment of respiratory infections in children. It is noteworthy that most of these studies were conducted in developed countries, with basic sanitation, health care, and strict, well-established and well-organized guidelines on the use of probiotics. Adverse effects were rarely reported, demonstrating probiotics to be safe. CONCLUSIONS: Despite the encouraging results - reducing new episodes of respiratory infections - the authors emphasize the need for further research, especially in developing countries, where rates of respiratory infections in children are higher when compared to the high per capita-income countries identified in this review.